Provision of long-acting reversible contraception in HIV-prevalent countries: results from nationally representative surveys in southern Africa - Morse, J (2013)
OBJECTIVE: To analyse the current provision of long-acting reversible contraception (LARC) and clinician training needs in HIV-prevalent settings. DESIGN: Nationally representative survey of clinicians. SETTING: HIV-prevalent settings in South Africa and Zimbabwe. POPULATION: Clinicians in South Africa and Zimbabwe. METHODS: Nationally representative surveys of clinicians were conducted in South Africa and Zimbabwe (n = 1444) to assess current clinical practice in the provision of LARC in HIV-prevalent settings. Multivariable logistic regression was used to analyse contraceptive provision and clinician training needs. MAIN OUTCOME MEASURE: Multivariable logistic regression of contraceptive provision and clinician training needs. RESULTS: Provision of the most effective reversible contraceptives is limited: only 14% of clinicians provide copper intrauterine devices (IUDs), 4% levonorgestrel-releasing IUDs and 16% contraceptive implants. Clinicians’ perceptions of patient eligibility for IUD use were overly restrictive, especially related to HIV risks. Less than 5% reported that IUDs were appropriate for women at high risk of HIV or for HIV-positive women, contrary to evidence-based guidelines. Only 15% viewed implants as appropriate for women at risk of HIV. Most clinicians (82%), however, felt that IUDs were underused by patients, and over half desired additional training on LARC methods. Logistic regression analysis showed that LARC provision was largely restricted to physicians, hospital settings and urban areas. Results also showed that clinicians in rural areas and clinics, including nurses, were especially interested in training. CONCLUSIONS: Clinician competency in LARC provision is important in southern Africa, given the low use of methods and high rates of unintended pregnancy among HIV-positive and at-risk women. Despite low provision, clinician interest is high, suggesting the need for increased evidence-based training in LARC to reduce unintended pregnancy and associated morbidities.